The mechanisms and application prospects of exosomes in acute myocardial infarction - Peng Zhou; Jia Zhang; Leilei Zhang; Jiangwei Yan; Chen Fang (Extracellular Vesicle)
Acute myocardial infarction (AMI) is a significant cause of death in cardiovascular diseases and an important topic in forensic pathology. It triggers various cellular pathological changes, leading to ventricular remodeling, changes in cardiac function, and, in severe cases, death. Current biomarkers for AMI lack specificity and can be influenced by various factors, making them challenging for diagnosis and differentiation. Exosomes, small vesicles with a lipid bilayer membrane, have emerged as potential biomarkers and therapeutic targets for AMI. They play a crucial role in intercellular cargo transport and communication. Exosomes play a dual role in cellular processes, exhibiting protective mechanisms under normal conditions while also contributing to disease progression in pathological contexts. This paper summarizes the mechanisms, research strategies, and application prospects of exosomes in AMI, providing insights for forensic investigations.